Pair distribution function analysis of nanostructural deformation of calcium silicate hydrate under compressive stress. Issue 1 (5th September 2017) - Bae, Sungchul; Jee, Hyeonseok; Kanematsu, Manabu; Shiro, Ayumi; Machida, Akihiko; Watanuki, Tetsu; Shobu, Takahisa; Suzuki, Hiroshi
Abstract: Despite enormous interest in calcium silicate hydrate (C–S–H), its detailed atomic structure and intrinsic deformation under an external load are lacking. This study demonstrates the nanostructural deformation process of C–S–H in tricalcium silicate (C3 S) paste as a function of applied stress by interpreting atomic pair distribution function (PDF) based on in situ X‐ray scattering. Three different strains in C3 S paste under compression were compared using a strain gauge, Bragg peak shift, and the real space PDF. PDF refinement revealed that the C–S–H phase mostly contributed to PDF from 0 to 20 Å whereas crystalline phases dominated that beyond 20 Å. The short‐range atomic strains exhibited two regions for C–S–H: I) plastic deformation (0‐10 MPa) and II) linear elastic deformation (>10 MPa), whereas the long‐range deformation beyond 20 Å was similar to that of Ca(OH)2 . Below 10 MPa, the short‐range strain was caused by the densification of C–S–H induced by the removal of interlayer or gel‐pore water. The strain is likely to be recovered when the removed water returns to C–S–H.